Content of Chlorophyll, Antioxidants, and Metabolite Compounds in the Leaf Development Stage of Murraya koenigii (L.) Spreng - Juswardi Juswardi; Salsabila Ulya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Murraya koenigii (L.) Spreng is often known as Temurui or Curry as a local name in Indonesia, and has long been used in medicine and has as a potential as a multi-medicinal plant. Temurui as a producer of bioactivity has the antioxidant properties. This is due to the presence of metabolite compounds contained in the leaves of the Temurui plant. Leaves are organs that are always growing where chemical components such as chlorophyll in the leaves will also develop thereby affecting leaf metabolism in plants. This study aims to determine the contens of chlorophyll, contens of antioxidants and metabolite compounds in Temurui leaves at the level of leaf development. Different leaf extractions are also used to measure the antioxidant, chlorophyll content and metabolite compounds found in Temurui leaves. The research results obtained on young, and old Temurui leaves obtained a total of 3 groups of dominant compounds, terpenoids, organic acids and esters, and mature leaves not find ester compound. The level of leaf development affects the contents of antioxidants and chlorophyll contents. Chlorophyll content in mature leaves was 44.60ug/ml, young leaves were 41.28ug/ml and old leaves were 30.27ug/ml while antioxidant contents in young leaves were 8.949ppm, mature leaves were 8.85ppm and old leaves were 8.429ppm.